MATH SOLVE

2 months ago

Q:
# Multiply: (5x − 2)(4x2 − 3x − 2)

Accepted Solution

A:

Hello there!

(5x - 2)(4x² - 3x - 2)

Use the distributive property

=(5x)(4x²) + (5x)(-3x) + (5x)(-2) + (-2)(4x²) + (-2)(-3x)² + (-2)(-2)

= 20x³ - 15x² - 10x - 8x² + 6x + 4

= 20x³ - 23x² -4x + 4

As always, it is my pleasure to help students like you. Let me know if you have any questions.

(5x - 2)(4x² - 3x - 2)

Use the distributive property

=(5x)(4x²) + (5x)(-3x) + (5x)(-2) + (-2)(4x²) + (-2)(-3x)² + (-2)(-2)

= 20x³ - 15x² - 10x - 8x² + 6x + 4

= 20x³ - 23x² -4x + 4

As always, it is my pleasure to help students like you. Let me know if you have any questions.